Weakening of Jupiter's main auroral emission during January 2014. Issue 3 (10th February 2016) - Badman, S. V.; Bonfond, B.; Fujimoto, M.; Gray, R. L.; Kasaba, Y.; Kasahara, S.; Kimura, T.; Melin, H.; Nichols, J. D.; Steffl, A. J.; Tao, C.; Tsuchiya, F.; et al.
Abstract: In January 2014 Jupiter's FUV main auroral oval decreased its emitted power by 70% and shifted equatorward by ∼1°. Intense, low‐latitude features were also detected. The decrease in emitted power is attributed to a decrease in auroral current density rather than electron energy. This could be caused by a decrease in the source electron density, an order of magnitude increase in the source electron thermal energy, or a combination of these. Both can be explained either by expansion of the magnetosphere or by an increase in the inward transport of hot plasma through the middle magnetosphere and its interchange with cold flux tubes moving outward. In the latter case the hot plasma could have increased the electron temperature in the source region and produced the intense, low‐latitude features, while the increased cold plasma transport rate produced the shift of the main oval. Key Points: Jupiter's auroral power decreased by 70% over 2 weeks of observations by the Hubble Space Telescope Could be caused by expansion of the magnetosphere or increase in hot plasma transport Aurora is variable without enhanced Io volcanism or solar wind pressure implications for Juno